Economic and Social Changes in the Demographic Structure of Romania - Puscaciu, Rose-Marie (EuroEconomica, 2025)
This article aims to capture a series of changes recorded in the demographic structure of Romania as a result of the transition from a centralized economy to a market economy. It is a known fact – which it was started from – that in the pre-1989 time, there was a balanced development strategy for all areas of Romania. A harmonious development of all areas of a country contributes to a balanced capitalization of local potential and, last but not least, to a unitary economic and social development throughout the entire territory of a country. Comparatively, the demographic results recorded in Romania after the transition to a market economy are analyzed in order to detect both the level of concentration of some economic indicators, and the trends recorded by them. This research will be carried out on the basis of a statistical toolkit, combined with graphical analysis. In this sense, the R studio software will be used, whose tools will be incorporated into the content of the article. In this way, it is considered that this article can contribute to the popularization of this particularly useful software in economic research.